Sleep Deprivation among Malaysian Students and the Impacts on Their Academic Performances: A Case Study - Muhammad Hiqmal Murad; Aini Syahira Jamaluddin (IJECA (International Journal of Education and Curriculum Application), 2024)
University students typically lack sleep owing to academic, social, and personal stresses. Sleep deprivation affects academic performance, cognition, attendance, and well-being. Sleep deprivation trends among local students at an international institution are examined and how it affects their academic performance. It seeks to understand sleep deprivation and its effects on grades, attendance, cognitive abilities, and well-being. Six students answered this qualitative research voluntarily. To guarantee student diversity, responders were chosen selectively. Semi-structured interviews with surveys and in-depth questions were used to produce comprehensive data. Two months were spent collecting data. The data were analysed using thematic analysis to discover sleep deprivation patterns and variables. Results indicate a clear link between poor sleep and academic achievement. Academic burden, extracurricular activities, and screen time greatly affected students' sleep and night time practices. These variables affected their academic success, university involvement, and well-being. Understanding university student sleep deprivation patterns and causes might help create treatments and support services to mitigate its effects. These findings suggest that university policy should promote good sleep habits, regulate academic demands, and decrease screen time to improve student well-being and academic achievement.